2010
DOI: 10.1016/j.apmr.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study on Oxygen Consumption On-kinetics During Treadmill Walking in Women With Systemic Lupus Erythematosus

Abstract: Objective To determine if oxygen consumption (VO2) on-kinetics differed between groups of women with systemic lupus erythematosus (SLE) and sedentary but otherwise healthy controls. Design Exploratory case control study. Setting Medical school exercise physiology laboratory. Participants Convenience samples of 12 women with SLE and 10 sedentary but otherwise healthy controls. Intervention None. Main Outcome Measurements VO2 on-kinetics indices including time to steady state, rate constant, mean respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…increased over time, and in healthy subjects it is known that training induces an acceleration of the VO 2 on-kinetics at the same absolute work load. 68 Furthermore, Keyser et al 69 demonstrated that VO 2 on-kinetics was slower in women with SLE. However, whether or not a physical activity intervention could normalize such an abnormality in patients with SLE has not yet been tested.…”
Section: Discussionmentioning
confidence: 99%
“…increased over time, and in healthy subjects it is known that training induces an acceleration of the VO 2 on-kinetics at the same absolute work load. 68 Furthermore, Keyser et al 69 demonstrated that VO 2 on-kinetics was slower in women with SLE. However, whether or not a physical activity intervention could normalize such an abnormality in patients with SLE has not yet been tested.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors observed that VO 2 at anaerobic threshold was 27.9% lower in women with SLE compared to controls (VO 2AT =12.9 ± 2.9 vs. 17.9 ± 3.1 ml/kg/min, respectively). These findings, suggest impaired microcirculatory dynamics and mitochondrial function during exercise, resulting in decreased a-vO 2 difference [30]. In this regard, previous studies have demonstrated that pathological adaptations in the muscle capillary bed of patients with SLE could impair microvascular reactivity and O 2 diffusive transport from muscle capillaries to mitochondria [31,32].…”
Section: Aerobic Capacity In Sle Patientsmentioning
confidence: 92%
“…Lastly, with regard to peripheral abnormalities, previous studies have demonstrated oxidative metabolism impairment in SLE patients compared with healthy controls [21,30]. Kayser et al [30], for instance, found prolonged VO 2 on-kinetics on the square wave test in SLE patients.…”
Section: Aerobic Capacity In Sle Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible relationship between excess CO 2 expiration and running performance [ 17 ] has also been suggested and concurrent increases in the time (AT-time) required to achieve the anaerobic threshold (expressed as relative O 2 ; AT- O 2 ), distance attained on a timed walk test, and improvement peak and submaximal O 2 /work rate ratio [ 20 ] following aerobic exercise training, even though no significant improvement in peak oxygen consumption was observed, have been reported. Moreover, AT- O 2 has been indirectly associated with Fatigue Severity Scale scores and the ability to meet energy requirements of instrumental activities of daily living [ 19 ]. However, CO 2 relationships have been less frequently considered and are less well understood.…”
Section: Introductionmentioning
confidence: 99%